2009
DOI: 10.5137/1019-5149.jtn.2231-09.1
|View full text |Cite
|
Sign up to set email alerts
|

Chronic ossified epidural hematoma after ventriculoperitoneal shunt insertion. a case report

Abstract: Chronic calcified/ossified epidural hematoma is an uncommon complication of ventricular shunt surgery. There are only 4 cases related to valve-regulated shunt operations in the literature. It may be seen especially in young patients with chronic hydrocephalus, probably due to craniocerebral disproportion. The precise mechanism of the calcification or ossification of the hematoma is not known, however, the dura mater seems to play a part in this process. A 17-year-old girl with triventricular hydrocephalus was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 17 publications
0
26
0
Order By: Relevance
“…6 Seyithanoglu et al reported that skull-dura adhesions are more prominent than dura-arachnoid adhesions in some patients, thus bleeding occurs in the epidural space instead of the subdural space due to cerebrospinal fluid overdrainage. 12 Other possible causes of hematoma include a coexistent bleeding disorder, bleeding from an occult dural vascular malformation and head trauma after surgery. 10 In our first case, rapid intracranial pressure reduction with VPS could have led to detachment of the dura from the calvarium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Seyithanoglu et al reported that skull-dura adhesions are more prominent than dura-arachnoid adhesions in some patients, thus bleeding occurs in the epidural space instead of the subdural space due to cerebrospinal fluid overdrainage. 12 Other possible causes of hematoma include a coexistent bleeding disorder, bleeding from an occult dural vascular malformation and head trauma after surgery. 10 In our first case, rapid intracranial pressure reduction with VPS could have led to detachment of the dura from the calvarium.…”
Section: Discussionmentioning
confidence: 99%
“…10 Consequently, cases of chronic, calcified epidural hematomas after ventricular drainage have been reported. 12,18 EDH is a well-known complication of the VPS procedure. Louzada et al suggested using a programmable valve to prevent hematomas.…”
Section: Discussionmentioning
confidence: 99%
“…[3] Most of these cases had acute hematomas, and only five of them had chronic calcified/ossified hematomas. [4] These patients were 15-35 years old. EDH contralateral to the VP shunt has been also described.…”
Section: Discussionmentioning
confidence: 99%
“…However, the diagnosis may be delayed in a case with VP shunt insertion because of a reduction in CSF volume in the ventricles via a properly functioning shunt [6]. The most common initial symptom is a headache, and there may be seizures in delayed cases [6].…”
Section: Case Reportmentioning
confidence: 99%